Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.21873/invivo.12111
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact of Coagulation Activity in Patients Undergoing Curative Resection for Pancreatic Ductal Adenocarcinoma

Abstract: Background/Aim: The aim of this study was to elucidate the clinical impact of coagulation disorders on outcomes after curative resection of pancreatic ductal adenocarcinoma. Patients and Methods: Preoperative coagulation activity in 135 patients, who had undergone curative resections for pancreatic ductal adenocarcinoma was retrospectively evaluated and the impact on survival outcomes analyzed. Results: A prolonged prothrombin timeinternational normalized ratio (PT-INR) (≥1.1) was detected in 23/135 patients (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
(14 reference statements)
1
3
0
Order By: Relevance
“…( 15 ) In addition, extended PT-INR was related to shortened recurrence-free survival and overall survival, rendering it a predictive factor of overall survival in patients with pancreatic ductal adenocarcinoma who had undergone curative resection. ( 16 ) Our findings are somewhat compatible with the aforementioned findings; specifically, a greater PT-INR was shown to be related to an increased risk of in-hospital mortality in critically ill patients with tumors who were treated in the ICU. In contrast to previous investigations, our study cohort consisted of severely ill individuals with tumors, and the previous research findings cannot be generalized to this patient group, as it consists of diverse kinds of malignancies rather than specific malignancies in previous studies.…”
Section: Discussionsupporting
confidence: 91%
“…( 15 ) In addition, extended PT-INR was related to shortened recurrence-free survival and overall survival, rendering it a predictive factor of overall survival in patients with pancreatic ductal adenocarcinoma who had undergone curative resection. ( 16 ) Our findings are somewhat compatible with the aforementioned findings; specifically, a greater PT-INR was shown to be related to an increased risk of in-hospital mortality in critically ill patients with tumors who were treated in the ICU. In contrast to previous investigations, our study cohort consisted of severely ill individuals with tumors, and the previous research findings cannot be generalized to this patient group, as it consists of diverse kinds of malignancies rather than specific malignancies in previous studies.…”
Section: Discussionsupporting
confidence: 91%
“…D-dimer was the end product of fibrinolytic degradation catalyzed by a fibrinolytic enzyme, which could reflect the synthesis status of fibrinolytic enzyme and thrombin in the body, and the increase of its level indicated the existence of hypercoagulability and secondary fibrinolytic hyperactivity in the body [ 15 ]. The increase of plasma D-dimer after surgery suggested that the patient's coagulation and fibrinolysis system were dysfunctional, and abnormal coagulation could induce tumor recurrence [ 16 ]. In addition, D-dimer was generally low in healthy people but high in lung cancer patients, and its level increased with the increase of TNM stage [ 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although many serum markers for the diagnosis of PDAC have been evaluated, to date, no reliable biomolecules (such as CEA, CA19.9, CA242) [ 30 ] have been identified for optimal clinical management. A notable push in this direction has been provided by recent studies focused on new biomolecules showing more reliable diagnostic performance [ 6 , 31 , 32 ]. Among these, the most promising is PIVKA-II protein, a modified prothrombin whose expression is related to vitamin K deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…In this scenario, circulating biomarkers, due to their availability, repr a powerful tool for early-stage diagnosis, prognosis, and follow up. Although many s markers for the diagnosis of PDAC have been evaluated, to date, no reliable biomole (such as CEA, CA19.9, CA242) [30] have been identified for optimal clinical managem A notable push in this direction has been provided by recent studies focused on new molecules showing more reliable diagnostic performance [6,31,32]. Among these, the…”
Section: Discussionmentioning
confidence: 99%